Pharmacological features of Beta-hydroxy-L-Glutamic acid receptors - Li, Philipp Novales (1990)
Beta-hydroxy-L-glutamic acid (L-BHGA),not L-glutamic acid, is markedly effective in Achatina giant neurones, to elucidate the L-BHGA conformation-activity relationship and the functional roles of the beta-hydroxyl group (B-OH), I examined the effects of stereoisomers of the novel L-BHGA analogue confirmationally fixed in extended or foleded forms alpha(carboxycyclopropyl)glycine ) L-ACCG, on five L-BHGA sensitive neurones. The receptors were classified into : BHG 1 are inhibited by L-BHGA analogue conformationally fixed in extended form, whereas 1B by threo-L compound in folded form. The B-OH role for BHG1 is to fix L-BHGA in extended (for 1A) or folded (for 1B) forms. BHG 2 are activated by L-BHGA ;2A is affected by erythro-L compound of which form is yet undetermined, whereas 2B is activated by threo-L compound in folded forms, the B-OH role for the former is probably as a proton donor-acceptor and for the latter is to fix L-BHGA in folded form. BHG 3, inhibited by L-BHGA, is activated mainly by threo-L compound in undermined form.
Includes bibliographical references (pages 81-82)
Keywords: Medicine